2012
DOI: 10.3357/asem.3120.2012
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Wake Differences in Heart Rate Variability During a 105-Day Simulated Mission to Mars

Abstract: The observed autonomic changes during confinement reflect an increase in parasympathetic activity during wake periods. Several factors could account for this observation, including reduced daylight exposure related to the confinement situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 23 publications
4
26
1
Order By: Relevance
“…Similarly, in the context of the Mars500 pilot study (Mars105), we observed that a 105-d period of confi nement was associated with an increase in parasympathetic activity during wakefulness. No signifi cant differences were found in the length or phase of the sleep-wake periods ( 25 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the context of the Mars500 pilot study (Mars105), we observed that a 105-d period of confi nement was associated with an increase in parasympathetic activity during wakefulness. No signifi cant differences were found in the length or phase of the sleep-wake periods ( 25 ).…”
mentioning
confidence: 99%
“…In this regard, the Mars500 project was conceived to gather data, knowledge, and experience about the psychological and physiological effects of living in an enclosed environment during 520 d as would be required for a real mission to Mars. This allows us to study the effect of long term confi nement without the infl uence of microgravity ( 25 ). Although autonomic nervous system (ANS) activity may play a key role in adaptation during space missions ( 2 ), little is known about the specifi c impact of confi nement on the circadian rhythm of ANS activity.…”
mentioning
confidence: 99%
“…In [11], the authors present a brief retrospective of the study of HRV in the scope of sleep studies and show detailed data on the variation of the HRV across the different sleep stages. Recent studies focus on nocturnal HRV under confinement conditions [12], and in [13], an in depth review of the relationship between HRV and several sleep disorders is presented.…”
Section: Introductionmentioning
confidence: 99%
“…This is important for future study of alertness in TBI, pointing to the relationship betweentopdown control processes governing arousal and sustained attention decrement [37,38]. Interestingly, research that investigated whether sleep-wake variations in the autonomic control of the heart are specifically altered by long-term confinement during a 105-day simulated mission to Mars, observed that autonomic changes during confinement reflected an increase in parasympathetic activity during wake periods [39]. The results from this study may be applicable to our population since the increase in low frequency heart rate variability and high frequency heart rate variability, as seen during confinement, was related to decreased attention processing, an outcome evaluated through an attentional load test.…”
mentioning
confidence: 99%
“…These objective physiological measures can be used to characterize differences in performance efficiency and in ability to adapt to working environments after TBI. In turn, fatiguerelated performance decrements caused by sleep loss or sustained attention might be improved with training to regulate responses, including autonomic and central nervous system parameters [39]. Further, psychiatric disorders such as major depressive disorder, anxiety, and substance abuse thataffect sleep and consequently alertness should be further studied, since they can playprimary, contributing, or exacerbating roles.…”
mentioning
confidence: 99%